GENERACIÓN DE POLINOMIOS DE SCHUBERT CON COCOA I: DIAGRAMAS DE ROTHE - Novoa Ramírez, Jesús Fernando; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2003)
We present a program for computing Schubert polynomials using Rothe diagrams. This program runs incv the computational algebraic system CoCoA,